Indonesian Reading and Writing Training to improve the literacy of children of Indonesian Migrant Workers (PMI) in Malaysia - Fiya Ainur Rohmatika; Ni Made Dwi Maharani; Muhamad Ershad; Mellia Dewi Hartono Soehardjo; Angelia Yuliana Dewi; Aulia Rivansy Nasution; Siti Nur Azizah (Journal of Society, Community and Business Development, 2024)
Indonesian, as the national language, plays a vital role in uniting various tribes and cultures spread throughout Indonesia. As a language used in everyday life, mastering Indonesian makes it easier for children to interact with the surrounding environment. They are facing big challenges in developing Indonesian language literacy. One of the main problems is the need for more access to books and learning materials in Indonesian. This activity aims to improve the reading and writing skills of PMI children in Malaysia so that they are more fluent in Indonesian. Through a holistic, interactive, and relevant approach to the life context of PMI children, this program proves that investment in language education can provide great benefits for the literacy development and social welfare of migrant children. Indonesian reading and writing training has a significant impact on increasing the literacy of PMI children in Malaysia. The results of this training showed a significant improvement in the reading and writing abilities of PMI children, as well as an increase in their confidence in using Indonesian in various contexts. Apart from that, this training also has a positive impact on strengthening the cultural identity of PMI children, helping them to maintain their cultural heritage in a different environment.